Penerapan Metode Problem Solving dalam Pembelajaran PAI: Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa di SMPN 15 Bandung - Sri, Afifah Rufianti; Fakhruddin, Agus; Surahman, Cucu (Jurnal Pendidikan Islam, 2024)
The problem solving method in Islamic Religious Education (PAI) learning aims to increase students’ understanding of problems, develop skills in finding creative solutions, and improve critical thinking abilities. This research aims to determine the application of learning using the Problem Solving method in PAI subjects at SMPN 15 Bandung. By using a qualitative descriptive design, researchers as key instruments used observation, interviews and documentation in collecting research data. To ensure the validity of the data, researchers used triangulation. The results of the research show that SMPN 15 Bandung has implemented a learning process using problem solving methods in PAI subjects. This is based on the fact that every student must dare to express an opinion and start thinking critically. The stages of applying problem solving methods in PAI learning include learning design, learning steps, and learning evaluation. Teachers have an important role in preparing the Learning Implementation Plan (RPP) and carrying out learning steps, from observing to communicating. Learning evaluation is carried out through authentic assessments that cover three domains: cognitive, affective and psychomotor.